The effect of superposition of residual and exploitation stresses on the state of stress of the circular welded seam of a tank-waggon - Palić, Vlastimir; Bela, Sabo; Alanović, J. (Journal of Production Engineering, 1992)
This paper presents the results of an investigation into the effect of superimposing residual and operational stresses on the stress state of a circular welded seam in a tank-wagon. The residual stress, induced by the welding process, was experimentally determined through the cut measuring elements method. The analysis considered the combination of residual and calculated operational stresses, as well as the superimposition of residual and calculated test pressure stresses, with the values of operational and test pressure stresses derived from the tank-wagon’s manufacturer documentation. The findings revealed that superimposing residual and operational stresses led to the surpassing of permissible stress levels along the weld’s axis. Additionally, the superposition of residual and test pressure stresses not only exceeded permissible stress but also exceeded the material’s yield strength in the weld’s axis. Consequently, the study concludes that the interaction between residual and operational stresses, especially when combined with test pressure stresses, significantly influences the tank-wagon’s operational safety. The paper includes tables and graphs displaying the measured and calculated stress values for nine measuring elements across the circular welded seam, focusing on a tank-wagon constructed from microalloyed steel StE 500 designed for ammonia transportation.